Similar Facts in the Supreme Court - Nair, Pushpa (Journal of Malaysian and Comparative Law, 2019)
In Wong Yew Ming v PP the Supreme Court was given a rare opportunity to consider the meaning and scope of section 15 of the Evidence Act 1950 (hereinafter referred to as ’the Act’) and hence the applicable rules with regard to similar fact evidence in Malaysia. Unfortunately this opportunity was not made use of with the result that similar fact evidence in Malaysia remains a mass of contradictory principles where reference to the Evidence Act is at best scanty and at worst non-existent.